Evaluation of circulating fibroblast growth factor 21 and Fetuin-a levels in type 2 diabetic patients with nephropathy And their relations to insulin resistance (Funded Work) - ADEL M. ASSIRI,; MOHAMED H. MAHFOUZ, (International Journal of Pharma and Bio Sciences, 2017)
Early detection of the risk factors of diabetic nephropathy before advanced renal damage remains a major challenge, so biomarkers related to diabetic nephropathy are required. Our aim was to assess the levels of fibroblast growth factor 21 (FGF21) and fetuin-A as an early detector risk factors of nephropathy progression and also to explore the relationship between risk markers and glycemic control (HbA1c) on the one hand and lipid profile, insulin resistance, microalbuminuria and renal function tests on the other hand. A cross-sectional study with 200 participants. Each studied group included 50 subjects, conducted as group I: healthy control subjects were matched for age and gender as patients groups; group II: T2DM with normoalbuminuria [ACR (albumin/creatinine ratio) <30 mg/g creatinine]; group III: T2DM with microalbuminuria [ACR=30-300 mg/g creatinine]; group IV: T2DM with macroalbuminuria [ACR>300 mg/g creatinine]. Serum FGF21 and fetuin-A levels were measured using enzyme-linked immunosorbent assay. The plasma glucose, insulin, homeostasis model for the assessment of insulin resistance (HOMA-IR), HbA1c, lipids profile, urea, and creatinine levels were also measured. Plasma glucose, insulin, HbA1c levels and HOMA-IR were significantly elevated in T2DM groups as compared to the control group. These parameters represented pronounced increases in group III and IV as compared to group II. Significant elevation of total cholesterol, triacylglycerol as well as LDL-C and a significant reduction of HDL-C were reported in diabetic nephropathy as compared to groups I and II. The dramatic significant increase in FGF21 and fetuin-A levels were observed in diabetic patients with micro- and macroalbuminuria with a significant increase in all kidney function compared to those with a normoalbuminuric group. Elevated FGF21 and fetuin-A levels were parallel with the levels of diabetic biomarkers. FGF21 and fetuin-A were found to correlate positively with systolic blood pressure, glucose, HbA1c, HOMA-IR, cholesterol, triacylglycerol, LDL-C and kidney function tests in diabetic nephropathy groups. Serum FGF21 and fetuin-A levels are strongly associated with insulin resistance in T2DM with nephropathy and could be promising useful biomarkers for predicting nephropathy progression, especially at early stages of diabetic nephropathy. Furthermore, they may serve as a tool to monitor the impact of prevention and intervention on renal damage.